The political ideas of Lorenz Stein and their influence on Rudolf Gneist and Gustav Schmoller - Pope, GA (1985)
The thesis traces the development of the social and political ideas of Lorenz Stein (1815-1890), a north German social and political scientist. In the early 1840's in Paris, under the influence of the Young Hegelians and Saint-Simon, he decided to attempt to develop a ‘science of society'. During the revolution of 1848-49, Stein worked out a political theory, his theory of state and society, which tried to show how the monarchical state could be defended against social revolution. After the revolution, Rudolf Gneist (1816-1895), a Prussian liberal politician and constitutional theorist, applied Stein's theory to the study of English constitutional history. In doing so, Gneist produced a theory of local government, which he called 'Self government', which was supposed to answer the question, left unanswered by Stein, of how the antagonism between state and society was to be overcome. Gneist postulated Selfgovernment as an intermediate structure, in which the state fused with the strongest social class. Selfgovernment consisted of Verwaltung, an organic combination of powers, which was best carried out by honorary,unpaid office holding. Gneist's model was the English gentleman-magistrate of the eighteenth century. The thesis also treats the relation of the young economist and historian Gustav Schmoller (1838-1917) to Stein. Schmoller developed Stein's ideas on state,economy and society, but from a historical point of view. Like Stein in his later years, Schmoller concentrated on Verwaltung. Stein's theory of Verwaltung was legalistic and philosophical, whereas Schmoller's was more sociological. Stein, Gneist and Schmoller represent a current in German political thought which was authoritarian, yet socially liberal. They tried to render popular participation in government superfluous by developing the scientific foundations of a technically perfect, autonomous 'administrative' apparatus.